Laws, Plans and Intelligibility: Defending Legal Positivism - Jing Yan Lee (UCL Journal of Law and Jurisprudence, 2018)
The debate between legal positivists and antipositivists has progressed to new points of contention. In recent years, a new positivistic theory of law has been put forth by Scott J. Shapiro, called ‘The Planning Theory of Law’. This paper aims to demonstrate how the Planning Theory is able to withstand a powerful antipositivistic objection by Mark Greenberg that social facts, by themselves, are incapable of grounding legal facts in an intelligible manner. Building on David Plunkett’s reply to Mark Greenberg in ‘A Positivist Route for Explaining How Facts Make Law’ (2012), this paper demonstrates how conceptual facts provided to us by the Planning Theory are able to account for the intelligible and reason-based manner in which social facts ground legal facts, thereby creating law without appealing to value facts or morality. For full text, please click here
Keywords: Legal Positivism; Jurisprudence